Can Organizational Climate Stewardship Significantly Impact Employee Voice? The Mediating Role of Trust in Supervisors - Aulia Defi Risulianah; Widiya Dewi Anjaningrum (Jurnal Manajemen dan Keuangan, 2025)
The digital transition gacorwin has instigated substantial alterations in the publishing sector, necessitating adaptation from all organizational components. This research seeks to examine the mediating function of supervisory trust in the link between stewardship atmosphere and employee voice at PT. Litera Mediatama, Malang. The study population consisted of all 49 workers of the organization, using a saturation sample approach. Data were gathered using gacorwin surveys and processed with SmartPLS 4.1.0.8. The results show that (1) the stewardship climate did not have a meaningful direct effect on employee voice (β=0.098, p>0.05); (2) the stewardship climate had a strong positive effect on trust in supervisors (β=0.914, p<0.001); and (3) trust in supervisors completely mediated the relationship, having a significant indirect effect (β=0.748, p<0.001). The results indicate that gacorwin confidence in supervisors is essential for converting organizational atmosphere into active employee engagement. The practical consequences encompass (a) establishing leadership training programs centred on transparency, (b) instituting bidirectional feedback mechanisms, and (c) initiatives aimed at enhancing supervisor-subordinate relationships. This research enhances the literature by validating psychological processes (trust) as a conduit between organizational policy and employee behaviour within the creative sector setting. It is advisable to do more research with a more extensive sample size to enhance the external validity of the results.